Preattentive and Predictive Processing of Visual Motion - Constanze Schmitt (Nature Portfolio, 2018)
Abstract Interaction with the environment requires fast and reliable sensory processing. The visual system is confronted with a continuous flow of high-dimensional input (e.g. orientation, color, motion). From a theoretical point of view, it would be advantageous if critical information was processed independent of attentional load, i.e. preattentively. Here, we hypothesized that visual motion is such a critical signal and aimed for a neural signature of its preattentive encoding. Furthermore, we were interested in the neural correlates of predictability of linear motion trajectories based on the presence or absence of preceding motion. We presented a visual oddball paradigm and studied event-related potentials (ERPs). Stimuli were linearly moving Gabor patches that disappeared behind an occluder. The difference between deviant and standard trials was a trajectory change which happened behind the occluder in deviant trials only, inducing a prediction error. As hypothesized, we found a visual mismatch negativity-component over parietal and occipital electrodes. In a further condition, trials without preceding motion were presented in which the patch just appeared from behind the occluder and, hence, was not predictable. We found larger ERP-components for unpredictable stimuli. In summary, our results provide evidence for a preattentive and predictive processing of linear trajectories of visual motion.